Resistance to imidazolinone herbicides in weedy rice in Malaysia - Ruzmi, Rabiatuladawiyah (2019)
The IMI-herbicides rice package is among the most effective methods for weedy rice control nowadays. However, the sole dependence and ignorance on the appropriate use on imidazolinone herbicide (IMI-herbicides) in the IMI-herbicides rice package by rice growers has caused weedy rice to develop resistance to the herbicides. Thus, this study was conducted to elucidate the occurrence, level, and mechanisms endowing resistance to IMI-herbicides on field-reported resistant (R) weedy rice populations collected from three local Malaysian IMI-rice fields (A, B, and C). The R weedy rice populations were compared with a susceptible weedy rice population (S), an imidazolinone-resistant rice cultivar (IMI-rice), and a susceptible local rice cultivar (MR219). Dose-response experiments were conducted to evaluate the sensitivity of all of the populations (A, B, C, S, IMI-rice, and MR219) to commercial IMI-herbicides (premix of imazapic and imazapyr) in seed bioassay (imazapic evaluation for pre-emergence) and whole-plant bioassay (imazapyr evaluation for post-emergence). Seeds (in seed bioassay) and plants (in whole-plant bioassay) of all populations were treated with seven different dosages of IMI-herbicides. Based on the Resistance Index (RI) quantification in seed bioassay, A and B possessed high and moderate level of resistance to IMI-herbicides, respectively. Population C, S, and MR219 were all sensitive to the herbicides (susceptible). Similar with A, IMI-rice were highly resistant to IMI-herbicides with RI index values of 50.5. In whole-plant bioassay, population A, B, and C were resistant at low level to the herbicides. Meanwhile, S and MR219 were both sensitive to IMI-herbicides. IMI-rice recorded a moderate level of resistance to IMI-herbicides in whole-plant assessment. Conclusively, population A and B were more resistant to imazapic than imazapyr, while conversely, population C was more resistant to imazapyr than imazapic. S and MR219 populations were equally sensitive to both herbicides. IMI-rice was observed to be more resistant to imazapic than imazapyr. Molecular investigation was conducted by comparing acetohydroxyacid synthase (AHAS) gene sequences between R weedy rice (A, B, and C), S, IMI-rice, and MR219. The sequence of the 1884 base pair AHAS gene fragment showed that S and MR219 were 99% similar. Evidently, AHAS gene sequences of R weedy rice were identical to the IMI-rice, where the same amino acid substitution of Ser-653-Asn was revealed in both populations when compared to S. In vitro assays were conducted using standards for imidazolinone herbicides consisting of imazapic (99.3%) and imazapyr (99.6%) with seven concentrations (0, 0.001, 0.01, 0.1, 1, 10, and 100 μM). The results showed that the AHAS enzyme extracted from R populations and IMI-rice were less sensitive to IMI-herbicides in comparison to S and MR219. Cross-resistance to imazapic and imazapyr was also observed in R and IMI-rice populations in this assay. In conclusion, the basis of imidazolinone resistance in selected populations of Malaysian weedy rice was identified to be due to a Ser-653-Asn mutation that reduced sensitivity of the target site to IMI-herbicides. The current study presents the first report of resistance mechanism in weedy rice in Malaysian rice fields.